Prevalence of Listeria spp. with PRS Genes in Fresh Vegetables from Traditional Markets - A. Kaisar Adiwijaya Putra; Rizalinda Sjahril; Arif Santoso; Dianawaty Amiruddin; Andi Alfian Zainuddin; Firdaus Hamid (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2020)
Listeriosis is a foodborne infectious disease caused by Listeria monocytogenes and is considered a serious health problem, due to the severity of symptoms and a high mortality rate in worldwide This study aims to identify and determine the prevalence of Listeria species through prs gene screening of fresh vegetables distributed in several markets of Makassar City. A total of 57 fresh vegetable samples were collected from February to May 2019 in four traditional markets Makassar. The isolates is examines to phenotypically and genotypically Vitek and Multiplex PCR with prs and lmo1030 primer. Phenotype analysis did not show the presence of Listeria species, but the results of genotypic was found 8 positive prs gene samples (14.03%), consisting of 31.2% long beans, 18.2% cabbage, and 9.1% cucumber and. All Listeria species found in this study is Listeria monocytogenes. This study also provide information and additional data that prs genes can be used as screening genotype for identify Listeria species in fresh vegetables.